East-Siberian Zodchestvo Festival - 2012 - Tkacheva, Marina (project baikal, 2012)
Catalogue East-Siberian Zodchestvo Festival 2012Chronicle of the East-Siberian Zodchestvo Festival 2012Our Guest, Totan KuzembaevThe List of Participants of the East-Siberian Zodchestvo Festival XIIBuilt ProjectsUn-built ProjectsPropaganda of Architecture Creation of Young Architects and StudentsChildren’s Architectural and Artistic Creation